Prevalence of malaria and its risk factors in Sabah, Malaysia - Abdul Rahman Ramdzan; Aniza Ismail; M.Z. Zetty Sofia (Elseiver, 2020)
Objectives The aim of this study was to determine the prevalence of malaria in Sabah and its potential risk factors. Methods This cross-sectional study analysed secondary data obtained from the health clinics in Sabah, Malaysia from January to August 2016. The Pearson Chi-square test was used to analyse the relationships between malaria infection and socio-demographic characteristics. Multivariable logistic regression was performed in order to determine the risk factors for malaria in Sabah. Results Out of 1222 patients, 410 (33.6%) had a laboratory-confirmed malaria infection. Infection by Plasmodium knowlesi accounted for the majority of malaria reports in Sabah (n=340, 82.9%). Multivariable analysis indicated that males (prevalence odds ratio 0.023, 95% confidence interval 0.012-0.047) and those living in a rural area (prevalence odds ratio 0.004, 95% confidence interval 0.002-0.009) were at higher risk 24.0–95.9) and those living in a rural area (adjusted odds ratio 212.6, 95% confidence interval 105.8–427.2) were at higher risk of acquiring a malaria infection. Conclusions Malaria infections in Sabah, Malaysia are common, with P. knowlesi being the most common malaria parasite. The infection was associated with several socio-demographic and geographical factors. Thus, mitigation measures should be considered to address modifiable risk factors for malaria infection.